2017
DOI: 10.1159/000464429
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Enhances Immunosuppression by Inhibiting CD4+ Effector T Cell Function and Promoting Treg Activity

Abstract: Background/Aims: Hypoxia occurs in many pathological conditions, including inflammation and cancer. Within this context, hypoxia was shown to inhibit but also to promote T cell responses. Due to this controversial function, we aimed to explore whether an insufficient anti-tumour response during colitis-associated colon cancer could be ascribed to a hypoxic microenvironment. Methods: Colitis-associated colon cancer was induced in wildtype mice, and hypoxia as well as T cell immunity were analysed in the colonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(127 citation statements)
references
References 40 publications
8
108
0
Order By: Relevance
“…C). In another study in which mouse colons with colitis‐associated colon cancer (CAC) were observed to be more profoundly hypoxic than the colons of healthy mice, CAC mouse colons displayed an increased frequency of CD4 + Foxp3 + T cells and increased suppressive activity of CD4 + Foxp3 + T cells relative to the colons of healthy control mice (Fig. A).…”
Section: Involvement Of Hif‐1α In Tregs Development and Functionmentioning
confidence: 95%
See 1 more Smart Citation
“…C). In another study in which mouse colons with colitis‐associated colon cancer (CAC) were observed to be more profoundly hypoxic than the colons of healthy mice, CAC mouse colons displayed an increased frequency of CD4 + Foxp3 + T cells and increased suppressive activity of CD4 + Foxp3 + T cells relative to the colons of healthy control mice (Fig. A).…”
Section: Involvement Of Hif‐1α In Tregs Development and Functionmentioning
confidence: 95%
“…Similarly, in non‐small cell lung cancer (NSCLC) patients, CD4 + CD25 + Tregs counts in peripheral blood are positively correlated with pathogenic grade and clinical stage of NSCLC and with the expression of HIF‐1α in NSCLC tissues . Despite the link between hypoxia and HIF‐1α in the colon and increased number and inhibitory activity of Tregs, the possibility that this effect is attributable to DC‐associated HIF‐1α, but not T cell‐associated HIF‐1α, cannot be excluded.…”
Section: Hif‐1α and Tregs In Pathogenic Microenvironmentsmentioning
confidence: 99%
“…Further, T-cell motility is reduced in hypoxia (74). In murine models of colorectal carcinoma, hypoxia reduced differentiation of CD4 þ T cells by 20% to 40%, while enhancing the number and function of Tregs (75). Hypoxic effector T cells exhibit decreased IFNg and IL2 production (62).…”
Section: Tumor Hypoxia and Innate And Adaptive Immune Functionmentioning
confidence: 99%
“…reported that severe hypoxia was accompanied by decreased differentiation of CD4+ effector T cells and increased numbers and enhanced suppressive activity of regulatory T cells. Moreover, T cell stimulation under hypoxic conditions inhibited the differentiation and proliferation of Th1 cells, as well as IFN‐γ production by Th1 cells, and enhanced the suppressive capacity of regulatory T cells . Based on these reports, we hypothesized that hypoxia may correlate to ACR in the following ways: (1) the low oxygen levels in the endothelial cells in the liver until the patients recovered from HPS may account for the correlation; or (2) although low oxygen saturation in patients with HPS before LT may enhance immunosuppression, drastic changes of the hypoxic condition after LT may change the T cell condition, possibly leading to immune stimulation.…”
Section: Discussionmentioning
confidence: 99%